Complete genomic characteristics and pathogenic analysis of the newly emerged classical swine fever virus in China - Zhang, Hongliang (BMC Vet Res, 2018)
BACKGROUND: Classical swine fever (CSF) is one of the most devastating and highly contagious viral diseases in the world. Since late 2014, outbreaks of a new sub-genotype 2.1d CSF virus (CSFV) had caused substantial economic losses in numbers of C-strain vaccinated swine farms in China. The objective of the present study was to explore the genomic characteristics and pathogenicity of the newly emerged CSFV isolates in China during 2014–2015. RESULTS: All the new 8 CSFV isolates belonged to genetic sub-genotype 2.1d. Some genomic variations or deletions were found in the UTRs and E2 of these new isolates. In addition, the pathogenicity of HLJ1 was less than Shimen, suggesting the HLJ1 of sub-genotype 2.1d may be a moderated pathogenic isolate and the C-strain vaccine can supply complete protection. CONCLUSIONS: The new CSFV isolates with unique genomic characteristics and moderate pathogenicity can be epidemic in many large-scale C-strain vaccinated swine farms. This study provides the information should be merited special attention on establishing prevention and control policies for CSF.